2011
DOI: 10.1186/1743-422x-8-329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclophilins alters lipid trafficking and blocks hepatitis C virus secretion

Abstract: Host cyclophilin (cyp) inhibitors, such as NIM811, efficiently inhibit replication of hepatitis C virus (HCV) and have shown significant promise in recent clinical trials for the treatment of chronic HCV. It is therefore important to fully understand the mechanism of action of these therapeutic agents. Data obtained from comprehensive systems biology approaches have led to the hypothesis that the antiviral activity of cyclophilin inhibitors is mediated through impairing the cellular machinery on which HCV reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…In the present study, HNF4␣ or PLA 2 GXIIB downregulation induced abnormal aggregation of large LDs and reduced the number of cytosolic LDs. Such LD rearrangement was accompanied by the reduced expression and distorted cytosolic distribution of HCV proteins, similar to that of nordihydroguaiaretic acid and cyclophilin inhibitors (33,34). These results echo the notion that cytosolic LDs are important organelles for HCV assembly and secretion (11).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, HNF4␣ or PLA 2 GXIIB downregulation induced abnormal aggregation of large LDs and reduced the number of cytosolic LDs. Such LD rearrangement was accompanied by the reduced expression and distorted cytosolic distribution of HCV proteins, similar to that of nordihydroguaiaretic acid and cyclophilin inhibitors (33,34). These results echo the notion that cytosolic LDs are important organelles for HCV assembly and secretion (11).…”
Section: Discussionsupporting
confidence: 76%
“…The rearrangement of LDs reportedly impairs HCV infectivity (32)(33)(34). Huh7.5.1 cells were infected with HCVmutJFH1 in the presence of bezafibrate and then observed under a confocal microscope at 72 h postinfection to investigate whether or not HNF4␣ regulates the rearrangement of LDs.…”
Section: Hnf4␣mentioning
confidence: 99%
“…Electron microscopy analyses suggest that NS5A-positive structures correspond, in part, to double membrane vesicles, which are a hallmark of the membranous HCV replication factory, designated membranous web (52). A NS5A "cluster" phenotype similar to that of the PW turn mutants was previously found in cells treated with NS5A or Cyp inhibitors (46,52,53), as well as in PI4KIII␣ knockdown cells. This phenotype was shown to correspond to lipid droplets or aberrant double membrane vesicles, respectively (47).…”
Section: Discussionmentioning
confidence: 93%
“…9B, right column). This altered phenotype correlated with a strong accumulation of large structures where NS5A is present, reminiscent of the cluster distribution in cells treated with NS5A and Cyp inhibitors (46,52,53). Notably, the proportion of cells with the cluster phenotype varied from 24 to 67% for I315G and P314A mutants, respectively, compared with 5% for WT (Fig.…”
mentioning
confidence: 91%
“…CyPA binding to, and presumably isomerization of, NS5A domain II has been proposed to change the local conformation of the CyPA-binding site (51), which in turn can "activate" NS5A to maintain the integrity of the viral replication complex (30). In addition, Anderson et al (2) reported a distinct change of localization and trafficking of lipid molecules upon CPI treatment. Because NS5A localizes to lipid droplets (LDs), possibly to influence viral assembly, CPIs might affect NS5A trafficking and HCV assembly as well (12,26).…”
mentioning
confidence: 99%